Inhibition of return is no hallmark of exogenous capture by unconscious cues - Fuchs, Isabella; Ansorge, Ulrich (Frontiers in Human Neuroscience, 2012)
Inhibition of irrelevant information and response tendencies is a central characteristic of conscious control and executive functions. However, recent theories in vision considered Inhibition of Return (IOR: slower responses to attended than unattended positions) to be a hallmark of automatic exogenous capture of visual attention by unconscious cues. In the present study, we show that an unconscious cue that exogenously captures attention does not lead to IOR. First of all, subliminal cues with a contrast different from a searched-for target contrast capture attention independently of their match of contrast polarity to the search criteria. This is found with a short cue-target interval (Exp. 1). However, the same cues do not lead to IOR with a long cue-target interval. The lack of IOR is also verified for several intermediate intervals (Exp. 2), for high-contrast cues and low-contrast targets (Exp. 3), and with lower luminance cues presented on a CRT screen (Exp. 4). Finally, no capture effect but IOR is found for consciously perceived anti-predictive cues (Exp. 5). Together the results support the notion of a double dissociation between IOR and exogenous capture and are in line with a decisive role of consciousness for inhibition.